2019
DOI: 10.3389/fimmu.2019.02875
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cellular Cytotoxicity (ADCC)-Mediating Antibodies Constrain Neutralizing Antibody Escape Pathway

Abstract: Both neutralization and antibody-dependent cellular cytotoxicity (ADCC) may be required for effective protection against HIV-1 infection. While there is extensive information on the targets of early neutralizing antibody (nAb) responses, much less is known about the targets of ADCC responses, which are more difficult to characterize. In four individuals recruited during acute HIV-infection, ADCC responses were detected 3-7 weeks prior to nAb responses. To determine the relative influence of ADCC and nAb respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Our stable transfected cell line expressed S protein on its surface with good consistency that decreases assay variability. Some studies show that strong association between the ADCC response and antibody binding on the target antigen on the surface of infected cells ( Karlsson et al, 2018 ; Mielke et al, 2019 ; Smalls-Mantey et al, 2012 ). In order to explore that antibody binding to the S target cells was proportional to the amount of cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our stable transfected cell line expressed S protein on its surface with good consistency that decreases assay variability. Some studies show that strong association between the ADCC response and antibody binding on the target antigen on the surface of infected cells ( Karlsson et al, 2018 ; Mielke et al, 2019 ; Smalls-Mantey et al, 2012 ). In order to explore that antibody binding to the S target cells was proportional to the amount of cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Infected-cell antibody binding assay. The binding of mAbs to the cells was measured as described previously (84). Briefly, 2 × 10 5 cells per well were incubated with 1 μg/mL mAb for 2 hours at 37°C followed by surface staining with anti-CD4-PerCP-Cy5.5 for 20 minutes at room temperature.…”
Section: Author Contributionsmentioning
confidence: 99%
“…For instance, one previous study suggested that neutralization pressure renders viruses ADCC susceptible. 45 Animal models may yield conflicting results because in general, the challenge stocks only contain cell-free virus that have demonstrated neutralization susceptibility to the passively infused antibody.…”
Section: Discussionmentioning
confidence: 99%